q+q=q*q

Simple and best practice solution for q+q=q*q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for q+q=q*q equation:



q+q=q*q
We move all terms to the left:
q+q-(q*q)=0
We add all the numbers together, and all the variables
q+q-(+q*q)=0
We add all the numbers together, and all the variables
2q-(+q*q)=0
We get rid of parentheses
2q-q*q=0
Wy multiply elements
-1q^2+2q=0
a = -1; b = 2; c = 0;
Δ = b2-4ac
Δ = 22-4·(-1)·0
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$q_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$q_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4}=2$
$q_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-2}{2*-1}=\frac{-4}{-2} =+2 $
$q_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+2}{2*-1}=\frac{0}{-2} =0 $

See similar equations:

| 4-6n=7-5n | | x-1.7=2.3 | | 5/3x+1/3x=102/3+8/3x | | 5x+3+2x=-2+2x-4 | | (3x+1)^2-100=0 | | 2a-5=13-4a | | x/5+3=22 | | 39-8x=11+6x | | X^2-3x+2=9 | | x/16+3=x/4+5/8 | | -5y-9=-(y+-1) | | -5y+-9=-(y+-1) | | 21/2n=10 | | -5x-13=6x-2 | | 6-7x=5x-9x+12 | | 3p+4-2p=9 | | w(w+56)=663 | | 12=-4/7y | | 3x+9-9=12-9= | | X3+-5x+6=4.2 | | 4x+5x-30=75-6x | | X-2x=5x | | x÷6+2=-5 | | 4x-(2x-10)=2 | | -16/9=-4/3(5/3+x) | | 5(2p+3)=3(4p+1)-2(3p+2) | | 7x+4=2×+5 | | 3/2-7/4x=-9/8 | | 2(1-3x)=3(5x+2) | | 1/5x-2=-2/3+x | | 6x+4x-54=36-8x | | 16=64^2n |

Equations solver categories